2023
DOI: 10.1038/s41416-023-02271-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends in cardiovascular burden among patients with prostate cancer receiving androgen deprivation therapy: a population-based cohort study

Abstract: Background Although androgen deprivation therapy (ADT) is associated with cardiovascular risks, the extent and temporal trends of cardiovascular burden amongst patients with prostate cancer receiving ADT are unclear. Methods This retrospective cohort study analyzed adults with PCa receiving ADT between 1993–2021 in Hong Kong, with follow-up until 31/9/2021 for the primary outcome of major adverse cardiovascular events (MACE; composite of cardiovascular mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Furthermore, some PCa medications, including ADT (androgen deprivation therapy), have a potency that adversely affects the cardiometabolic status and increases the risk for cardiovascular complications ( 33 36 ). Chan et al ( 37 ) recently demonstrated temporal increasing trends of recipients of ADT therapy with cardiovascular risk factors, frequently used cardiovascular and metabolic medications, and developed cardiovascular events. CVD is the leading cause of mortality in PCa survivors ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some PCa medications, including ADT (androgen deprivation therapy), have a potency that adversely affects the cardiometabolic status and increases the risk for cardiovascular complications ( 33 36 ). Chan et al ( 37 ) recently demonstrated temporal increasing trends of recipients of ADT therapy with cardiovascular risk factors, frequently used cardiovascular and metabolic medications, and developed cardiovascular events. CVD is the leading cause of mortality in PCa survivors ( 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data were acquired from the Clinical Data Analysis Reporting System (CDARS) of the Hong Kong Hospital Authority, a statutory body that manages all public hospitals and their affiliated outpatient and day care facilities in Hong Kong, covering approximately 90% of the population and being the most representative electronic medical database available in Hong Kong. 8 CDARS prospectively collects patient information including, but not limited to, demographic data, selected laboratory tests, diagnoses, drug prescriptions, procedures, and episodes of hospital visits since 1993. CDARS encodes diagnoses using the International Classification of Diseases, ninth revision (ICD-9), as CDARS has not implemented ICD-10 codes to date.…”
Section: Methodsmentioning
confidence: 99%
“… 14 , 15 , 16 , 17 Our team has previously used this cohort of PCa patients receiving ADT for studying cardiovascular outcomes. 18 , 19 , 20 …”
Section: Methodsmentioning
confidence: 99%